(In)visible children and COVID-19: human trafficking in public health ethics - Kahambing, Jan Gresil S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper appraises the link of public health ethics to human trafficking, especially on children. Taking from the more visible reports of child deaths from the virus, I focus on child health as an emphasis on how during this COVID-19 crisis, abuse and violence are also there albeit hidden. The range of clandestine operations concerning this issue in the Philippines seem to be broad and persistent. While local emergency ethics focuses on varying ways that contextualize – and locate special visible forms of – vulnerabilities from local citizens amid disasters, some vulnerabilities arise only within shrouded and surreptitious set-ups in public health ethics. Recognizing the hazards that lie in carefully categorizing visible and invisible vulnerabilities, human trafficking that preys on children is one invisible vulnerability that might gradually be pending in the sidelines. With the myriad of concerns on different fronts, there is a greater risk that this furtive issue might be treated subpar with other public health ethical considerations.